Analisis Penggunaan Konjungsi Dalam Rubrik Tajuk Rencana Harian Riau Pos edisi September 2020 - Vania Riwanti; Ermawati S (UIR Press, 2022)
This research is motivated by the many errors in newspaper writing regarding the use of conjunctions, including coordinating conjunctions and subordinating conjunctions. In accordance with this description, the formulation of the problem in this study relates to (1) how is the use of coordinating conjunctions in the September 2020 edition of the Riau Pos daily Tj, and (2) how is the use of subordinating conjunctions in the September 2020 edition of the Riau Pos daily Tajuk Rencana. This study aims to determine, analyze, and conclude the use of conjunctions in the September 2020 edition of the Riau Pos daily Tna. The population in this study is the September 2020 edition of the Riau Pos daily Tajuk Rencana. The technique used in this research is documentation technique, and hermeneutic technique. The theories used include (Alwi, et al., 2003), and (Chaer, 2015). This research is a qualitative research. The content analysis method used in this research is descriptive method. The results of this study can be concluded that there is the use of conjunctions in the daily rubik tajuk rencana Riau Pos totaling 352 data from 26 rubrics. The use of these conjunctions is divided into 254 coordinating conjunction data, and 112 subordinating conjunction data. Based on one example of the coordinating conjunction of addition (and, and) found in the sentence